Lignin-based carbon fiber: a current overview. (4th July 2018) - Souto, Felipe; Calado, Veronica; Pereira, Nei
Abstract: Research involving lignin use is not new. For many years, the macromolecule was underestimated in its potential and burned for energy use in pulp and paper industries. However, with the advent of biorefinery on the valorization of lignocellulosic fractions, lignin is receiving greater motivation to be researched. Of the many applications, the most profitable one is its conversion into carbon fiber. Lignin-based carbon fibers can reduce the manufacturing price of this fiber to values greater than 35%, besides using a renewable material with a highly sustainable appellation. This paper gives an overview about lignin-based carbon fiber comparing the process to current precursors, presenting different pathways on different research, pointing to the most common difficulties and assessing new findings. A gap not fully clarified yet is concerning the lignin structure and its relation to extrusion process. After isolation procedures, lignin repolymerizes in a different manner compared to when it is in its natural form. Some studies have shown that some organic functions, the molecular weight and the structure conformation of the lignin can favor or disfavor thermal mobility. Although it is known purification is considered a criterion that favors extrusion, there is no study involving a selection of parameters that improves thermal mobility. Herein, it is highlighted a set of desired structure properties that provides a very good thermal mobility and extrusion in order to obtain a lignin-based carbon fiber with good properties.